Hubungan antara Australia dan China di Kawasan Asia Pasifik. Studi Kasus: Ekspansionisme China di Asia Pasifik - Meita Ayu Nindyawati (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2020)
The existence and power of China in the international eye can no doubt. One of China's efforts expanded its wings to occur in the Asia-Pacific region. Of course, behind this is China's interests and some other implications that make China an expansionism in the security and economy of Asia Pacific. Australia's proximity to the United States as the largest political, economic and military actor in the Asia Pacific makes Australia's position to be stretched with the Asian-Pacific countries. It is also due to the presence of China as a new force in the Asia-Pacific region which is considered to be an American competitor who has been regarded as a country that has great control over the Asia Pacific through its proximity and assistance given to Australia. China's presence as a force of United States in the region is also due to several historical factors. In this article, the author seeks to describe and analyse how Australia and China relations in the Asia-Pacific region due to China's expansionism by using national security concepts and foreign policy theories. Keywords: Asia Pacific; economy; military; policy.